2016
DOI: 10.1002/jbm.a.35693
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenans effect on neutrophils alone and in combination with LPS in vitro

Abstract: Influence of sulfated red algal polysaccharides (κ-, λ-, and κ/β-carrageenans) and degraded derivative of κ/β-carrageenan on neutrophils/monocytes activation alone and in combination with lipopolysaccharide was investigated by means of determination of reactive oxygen species production, latex microparticles engulfment, total and extracellular myeloperoxidase induction and the analysis of silhouette and contour two-dimensional images of flattened cells. Carrageenans alone can activate neutrophils with much les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
3
16
0
3
Order By: Relevance
“…Earlier, we studied the effect of carrageenan on human neutrophils alone and in combination with LPS. 15 In accordance with our results, carrageenan alone was able to activate neutrophils with much less potency than LPS. At the same time, carrageenans with a high sulfate content have the most prominent effect in this manner.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Earlier, we studied the effect of carrageenan on human neutrophils alone and in combination with LPS. 15 In accordance with our results, carrageenan alone was able to activate neutrophils with much less potency than LPS. At the same time, carrageenans with a high sulfate content have the most prominent effect in this manner.…”
Section: Discussionsupporting
confidence: 91%
“…It has been found that carrageenan in vitro protects neutrophils against LPS‐induced killing . At the same time, reduced Density indicates a less solid cell body filling the area bounded by the convex hull.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations